2014
DOI: 10.3126/kumj.v10i4.10994
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Foetal Death and Its Probable Causes: Two Years Experience in Dhulikhel Hospital – Kathmandu University Hospital

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
7
12
1
1
Order By: Relevance
“…Study by Tariq et al 12 had not found any association between parity and gestational age. Maximum IUFD cases were belonged to 21-25 years (35.2%), same as study by Patel S et al 10 while Tamarkar SR 13 had reported higher stillbirth associated with increasing maternal age.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Study by Tariq et al 12 had not found any association between parity and gestational age. Maximum IUFD cases were belonged to 21-25 years (35.2%), same as study by Patel S et al 10 while Tamarkar SR 13 had reported higher stillbirth associated with increasing maternal age.…”
Section: Discussionsupporting
confidence: 73%
“…Study by Anjali C et al 8 Of all IUFD in our study 82.35% delivered were fresh and only 17.64% were macerated. Tamarkar SR 13 had observed majority of stillborn to be non-dysmorphic. We observed 56.86% male and 43.33% female babies and previous studies also suggested that male fetuses are more likely to suffer from antenatal hypoxia (ante-or intra-partum).…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes may be associated with an increased risk of macrosomia, congenital malformations, birth trauma and neonatal metabolic abnormalities 6,7 and still births. 8 Similarly, in the present study intrauterine death was observed in 12.5 % of the gestational diabetics. Further in this study we compared the baseline characteristics and renal parameters between gestational diabetics with normal fetus and gestational diabetics with intrauterine fetal death.…”
Section: Discussionsupporting
confidence: 81%
“…Tamrakar et al 8 have observed strong positive association between body mass index and still birth. However in the present study body mass index of gestational diabetics with intrauterine fetal death did not differ significantly compared to gestational diabetics with normal fetus.…”
Section: Discussionmentioning
confidence: 96%
“…Nayak SR reported that 58% cases autopsy added significantly to the diagnosis. 13 Preterm stillbirth with gestational age between 28-37 weeks was 114 (43%).Various studies have shown various incidence of prematurity in cases of stillbirth 44.4% ,34.05% 15,17 Prematurity was the cause or effect of fetal death was not evident in all cases.…”
Section: -14mentioning
confidence: 99%